Haiku : poetry ancient & modern :an anthology - Hardy, Jackie (MQ Publications, 2008)
The haiku is a tiny poem of Japanese origin, usually only three lines long and a total of seventeen syllables, that uses concrete images to create a sensation one can almost touch, smell and taste. Just as in nature, each poem is made up of fundamental building blocks that together form a living, breathing entity. The true beauty of haiku lies in its ability to capture an intensely human moment, mood or insight with a clarity and poignancy that can be lost in other verse forms. This inspiring anthology is a beautiful collection that brings together 136 of the best contemporary poets from around the world, and features traditional Japanese Masters such as the much loved Issa and Basho.